Circular Economy in the Agrifood Sector - PALTRINIERI, ROBERTA (Consumo, Comunicazione, Innovazione, 2022)
The circular economy is recognised as a new economic paradigm as opposed to the traditional linear open-ended economy model based on endless exploitation of resources and prioritising profit over sustainability. Aligning global production and consumption systems with sustainability is one of the major challenges of our time. Investments in renewable and clean energies, clean transport, sustainable food, and a smart circular economy remain significant opportunities for future economic growth prospects. This book results from the project Interreg Europe SinCE-AFC, which aims to provide horizontal mechanisms to enhance the capacity of Small and Medium-sized Enterprises to implement new production models and contribute to sustainable growth in the agri-food sector in the European Union. The main goal is to elaborate on theoretical and practical aspects of the circular economy in this sector, introducing the concept and its limitations, outlining the regulatory framework and the recent policy developments, and illustrating factors encouraging (or hindering) the transition. The book presents the main outcomes of the SinCE-AFC project, elaborating on the results of two surveys aimed at assessing the level of awareness, knowledge, engagement and needs of the project partners and local stakeholders. It also provides a systematisation of the collected good practices covering the entire supply chain, from the recovery of agricultural by-products to the digital app for food waste prevention. A summary of project partners’ action plans concludes, highlighting policies and actions implemented to improve the replicability of practices and shift the agri-food sector towards a more resilient and sustainable path.